Smooth Solutions of a Class of Quasielliptic Equations - Najafov, Alik M. (Sarajevo Journal of Mathematics, 2024)
In this paper the smoothness of solutions of one class of quasielliptic equations in the bounded domain GR^n satisfying the flexible λ-horn condition are studied. 2000 Mathematics Subject Classification. 35Q35, 35A15